Changes in voiding behavior in a mouse model of Alzheimer’s disease - Biallosterski, B. T.; Prickaerts, J.; Rahnama’i, M. S.; de Wachter, S.; van Koeveringe, G. A.; Meriaux, C. (Frontiers in Aging Neuroscience, 2015)
Besides cognitive decline and behavioral alteration, urinary incontinence often occurs in patients suffering from Alzheimer’s disease. To determine whether the transgenic mouse model of Alzheimer’s disease, APPSL/PS1M146L mouse, shows alteration of the urinary bladder function and anxiety, as for patients with Alzheimer’s disease, we examined the urinary marking behavior in relation to affective behavior. At 18 months of age voiding behavior of APPSL/PS1M146L (APP/PS1) and wild type (WT) mice was assessed by using a modified filter paper assay in combination with video tracing, with the cage divided into a center and corner zones. Anxiety-related behavior and locomotion were respectively tested in an elevated zero maze and an open field. The APP/PS1 mice urinated more in the center zone than the WT mice. The total volume of markings was significantly lower in the APP/PS1 mice. In both groups, the average volume of a marking in the corner zone was larger than in the center zone. In the elevated zero maze, the APP/PS1 mice spent less time in the open arms of the arena, considered as anxiogenic zones, than the WT mice. During the open field task, the APP/PS1 mice covered a longer distance than the WT mice. These findings show that the APP/PS1 mice have a different voiding behavior compared to the WT mice, i.e. urinating with small volumes and voiding in the center of the cage, and suggest that increased locomotor activity and anxiety-related behaviors are factors in the change in voiding pattern in the APP/PS1 mouse.